Assessing the driving forces for greening business practices: Empirical evidence from the United Arab Emirates' logistics service industry - L. Salhieh; I. Abushaikha (South African Journal of Business Management, 2016)
The uprising economic, social and political pressures on achieving a good level of environmental governance have forced companies to adopt business practices that aim to mitigate CO2 emissions. Logistics industry is considered as one of the major areas that could make a considerable improvement in reducing the environmental impact of business activities. The aim of this study is to investigate the driving forces that influence the adoption of environmentally friendly logistics activities. Following a detailed literature review, a theoretical model, which encompassed several driving forces and logistics activities, has been developed. Survey-based quantitative data were collected from logistics service providers in the United Arab Emirates (UAE) and analysed using structural equation modelling methodology and multiple regression analysis. Through answering 110 questionnaires, respondents holding different managerial levels at logistics service organizations, provided data reflecting their perception of the forces that would influence the adoption of green logisticspractices. The driving forces (legislations, customers, and organizational awareness) were found to influence the adoption of green logistics practices by the logistics service industry in the areas of warehousing, packaging and transportation.
Keywords: 650